An electrolyte-gated polythiophene transistor for the detection of biogenic amines in water. Issue 50 (31st May 2018) - Minamiki, Tsukuru; Hashima, Yuki; Sasaki, Yui; Minami, Tsuyoshi
Abstract : An ultra-low voltage operatable thin-film transistor based on a polythiophene pendant with a carboxy sidechain can detect biogenic amines in water. Abstract : We herein propose a novel sensing strategy for biogenic amines using an electrolyte-gated polythiophene transistor. This ultra-low voltage operatable device responds to amines on the basis of the molecular recognition ability of a polythiophene pendant with a carboxy side-chain, which indicates that the sensing platform can contribute to the realisation of easy-to-fabricate and integrated chemical sensors.